Current Status and Trends in Cabo Verde Agriculture - Monteiro, Filipa (2021)
With climate change, drought is expected to increase, and its negative impacts will be particularly important in developing countries, usually with rainfall-dependent agriculture. The Cabo Verde archipelago is characterized by limited resources, remoteness, vulnerability to natural disasters, and a fragile environment. In this study, we provide the first report of the current status and trends of agriculture in Cabo Verde. We present data on the current performance of agricultural production areas in these islands and discuss them in terms of their most important natural constraint, water. Also, we assess the impact of institutional strategies on crop production and evaluate recent mechanisms that have been engaged towards agrarian development in this archipelago. Our results show that, among the ten Cabo Verde Islands, Santiago has the largest area used for agriculture (52.5%), followed by Santo Antão (16%) and Fogo (15.8%), and that rainfed farming dominates in all of them. The staple crops, such as maize and beans, are produced through rainfed subsistence farming, whereas irrigated crops (i.e., sugarcane, tomatoes) are mostly grown for commercial purposes. The prolonged drought periods, exposure, erosion and soil degradation, which led to increasing desertification over the last decades, have been identified as the main constraints to agrarian development across the ten islands of the archipelago. The strategies of Cabo Verde government to mitigate water scarcity through small-scale irrigation based mainly on small dams and drip irrigation technology have a marked effect on agricultural production in the predominantly arid and semi-arid areas of this archipelago